RESEARCHING THE SCIENTIFIC HERITAGE OF MAHMUD ZAMAKHSHARI - S. S. Saidjalolov (Galaxy International Interdisciplinary Research Journal, 2021)
Purpose of the article: to study and analyze the centuries-old studies of the heritage of Mahmoud Zamakhshari. The introductory part provides an overview of research into the works of Zamakhshari and their authors. Information is given on the development of Zamahsharist studies in the East and West. The study of the works of the scientist in our country is highlighted. The Methods section explains the importance of the methods used in writing the article, such as historical analysis, analysis, synthesis, induction, deduction, and provides examples from the scholar’s legacy.